2011
DOI: 10.1063/1.3582133
|View full text |Cite
|
Sign up to set email alerts
|

Towards a programmable microfluidic valve: Formation dynamics of two-dimensional magnetic bead arrays in transient magnetic fields

Abstract: The induction of dipolar coupling has proven to allow for the initiation of self-assembled, reconfigurable particle clusters of superparamagnetic microbeads suspended in a carrier liquid. The adjustment of the interplay between magnetic and hydrodynamic forces opens various possibilities for guiding strategies of these superstructures within microfluidic devices. In this work, the formation dynamics of such particle clusters under the influence of a rotating magnetic field are studied. Different agglomeration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…Despite these differences, there is still an overall agreement in the trend of the master curve, consistent with t s ∝ Mn/ω. Previously, the clustering rate for magnetic particles in a rotating magnetic field was measured for three different frequencies by Wittbracht et al [28]. The investigators found that the clustering rate increased linearly with frequency which is also consistent with the scaling of Calderon and Melle (Eqn.…”
Section: Viscous Stresses Slow Clustering Dynamicssupporting
confidence: 71%
See 3 more Smart Citations
“…Despite these differences, there is still an overall agreement in the trend of the master curve, consistent with t s ∝ Mn/ω. Previously, the clustering rate for magnetic particles in a rotating magnetic field was measured for three different frequencies by Wittbracht et al [28]. The investigators found that the clustering rate increased linearly with frequency which is also consistent with the scaling of Calderon and Melle (Eqn.…”
Section: Viscous Stresses Slow Clustering Dynamicssupporting
confidence: 71%
“…Petousis et al showed there is a maximum length under which a chain is stable for a given Mn which scales as Mn −1/2 [21]. The unstable regime in which chains break apart and form two-dimensional clusters has only recently been explored [27,28,34]. Here, we present the correlation length of two-dimensional clusters L as a function of Mn.…”
Section: B Viscous Stresses Results In Smaller Clustersmentioning
confidence: 88%
See 2 more Smart Citations
“…3E). 40 However, due to the conned geometry (i.e., sphere-on-at), there is no formation of ordered 2D sheets and leading to only concentric rings when higher magnetic eld rotation frequency is employed (Fig. When the magnetic eld is rotated at low magnetic eld rotation frequency, the chain structures could also rotate (Fig.…”
Section: Resultsmentioning
confidence: 99%